Colonial Essence of Population Cencus in Uzbekistan SSR (In the Example of the 1939 Event) - Gulamov, Ilhomjon (International Journal on Orange Technologies, 2023)
This article deals with the 1939 census in the Uzbek SSR and details the goals of the Soviet census which based on the results of this event. The article discusses the planned socio-economic and political life in the country in the coming years. The article discusses the preparations for the census in the country and a number of its shortcomings, as well as a number of scientific conclusions and recommendations.